The Development Of Self-Employed Novice Entrepreneurs In Lampung Province, Indonesia - Yosy Arisandy; Ani Mekaniwati; Aang Munawar; Iwan Darmawan; Yose Rizal (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The empowerment of novice entrepreneurs is vital for fostering inclusive economic development and addressing structural unemployment in Indonesia. This study evaluates the effectiveness of the Independent Novice Entrepreneur Program (Tenaga Kerja Mandiri Pemula/TKMP) implemented by the Ministry of Manpower in Lampung Province. Using a mixed-methods approach, the research integrates quantitative data from surveys and progress reports with qualitative insights from interviews with mentors and participants. The program’s performance is assessed based on five Key Performance Indicators (KPIs): (1) production of goods/services, (2) implementation of marketing strategies, (3) maintenance of financial cash flow records, (4) acquisition of Business Identification Numbers (NIB), and (5) development of structured business plans. Findings reveal that the program exceeded the 60% achievement target across all KPIs, with the highest performance in product development (94.19%) and marketing strategy (91.60%). However, challenges remain in financial literacy, NIB registration, and long-term business sustainability. This study highlights the importance of continuous mentoring, digital literacy, and academic collaboration to strengthen entrepreneurial ecosystems at the local level. The results offer evidence-based recommendations for improving policy design and implementation of entrepreneurship support programs in developing regions. Keywords: novice entrepreneurs, entrepreneurship development, government program, business mentoring, financial literacy, digital marketing, Lampung Province, mixed-methods, policy evaluation, small business empowermen